Coastal and settlement typologies-based tsunami modeling along the northern Sumatra seismic gap zone for disaster risk reduction action plans. (December 2020) - Jihad, Abdi; Muksin, Umar; Syamsidik,; Suppasri, Anawat; Ramli, Marwan; Banyunegoro, Vrieslend H.
Abstract: Since after the 2004 Indian Ocean tsunami, multiple efforts have been carried out to investigate the occurrence potential of tsunami-generating earthquakes. One of the studies concluded that large earthquakes are expected to occur along the seismic gap zone in the west coast of Sumatra and thus have the potential to generate tsunamis. The objectives of the research are to (1) investigate the existence of the seismic gap zone and to calculate the potential energy of expected earthquakes along the zone; (2) develop a tsunami model based on the relation between tsunami amplitude, arrival time, and coastal and settlement typologies; and (3) suggest tsunami mitigation action plans for surrounding areas in order to reduce the risk of disaster. The earthquake distribution in Aceh indicates the presence of a seismic gap zone in the west coast of Aceh, indicated by the decrease in seismic activities within the area since 2008. The potential energy is equivalent to an Mw 8.7 earthquake. The earthquake has the potential to generate a tsunami with a maximum amplitude of 20 m in the west coast of Aceh. An analytic hierarchy process (AHP) analysis was applied to determine the hazard and vulnerability levels. Having the information of hazards and vulnerability, we derived the priority level of the study area and suggested the tsunami mitigation action that needs to be applied to the area. The results indicate that the AHP method gave stable results in the determination of the vulnerability, hazard, and priority levels and thus can be used for other regions of similar coastal and settlement typologies. The results also show that Banda Aceh, Calang, and Meulaboh cities are zones of priority level 1, where all components of tsunami action plans should be implemented, comprising (1) the provision of an early warning system and related information; (2) the construction of evacuation routes and buildings; (3) the improvement of knowledge of disaster risk; and (4) the strengthening of awareness and preparedness. All action plans should be applied for Blang Pidie, as the city is included in an area of priority level 2. For the areas with priority level 3, including Tapak Tuan, and Singkil, the government should improve knowledge of disaster risk and strengthen community awareness and preparedness.